How early life respiratory viral infections impact airway epithelial development and may lead to asthma - Berdnikovs, Sergejs; Newcomb, Dawn C.; Hartert, Tina V. (Frontiers in Pediatrics, 2024)
Childhood asthma is a common chronic disease of the airways that results from host and environment interactions. Most risk factor studies of asthma point to the first year of life as a susceptibility window of mucosal exposure that directly impacts the airway epithelium and airway epithelial cell development. The development of the airway epithelium, which forms a competent barrier resulting from coordinated interactions of different specialized cell subsets, occurs during a critical time frame in normal postnatal development in the first year of life. Understanding the normal and aberrant developmental trajectory of airway epithelial cells is important in identifying pathways that may contribute to barrier dysfunction and asthma pathogenesis. Respiratory viruses make first contact with and infect the airway mucosa. Human rhinovirus (HRV) and respiratory syncytial virus (RSV) are mucosal pathogens that are consistently identified as asthma risk factors. Respiratory viruses represent a unique early life exposure, different from passive irritant exposures which injure the developing airway epithelium. To replicate, respiratory viruses take over the host cell transcriptional and translational processes and exploit host cell energy metabolism. This takeover impacts the development and differentiation processes of airway epithelial cells. Therefore, delineating the mechanisms through which early life respiratory viral infections alter airway epithelial cell development will allow us to understand the maturation and heterogeneity of asthma and develop tools tailored to prevent disease in specific children. This review will summarize what is understood about the impact of early life respiratory viruses on the developing airway epithelium and define critical gaps in our knowledge.